2016
DOI: 10.1245/s10434-016-5229-9
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial Comparing Transperitoneal Versus Extraperitoneal Laparoscopic Aortic Lymphadenectomy for Surgical Staging of Endometrial and Ovarian Cancer: The STELLA Trial

Abstract: The STELLA trial is registered at the US National Institutes of Health (ClinicalTrials.gov) #NCT01810874.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
5
22
0
Order By: Relevance
“…We observed an intraoperative complication rate of 10.3% and an early postoperative complication rate of 26.5%. We found a higher rate of surgical morbidity in the conventional vs. robotic-assisted laparoscopy subgroup, findings that are consistent with previously reported results 4,5,24,42 .…”
Section: Main Findingssupporting
confidence: 92%
“…We observed an intraoperative complication rate of 10.3% and an early postoperative complication rate of 26.5%. We found a higher rate of surgical morbidity in the conventional vs. robotic-assisted laparoscopy subgroup, findings that are consistent with previously reported results 4,5,24,42 .…”
Section: Main Findingssupporting
confidence: 92%
“…Recently, a prospective randomized multicenter study (STELLA Trial) concluded that extraperitoneal and transperitoneal approaches to laparoscopic and robotic AL provide similar perioperative outcomes and lymph node yields. 34 The authors of this study also concluded that factors to be taken into account for choosing between extraperitoneal versus transperitoneal approach primarily include patient habitus, site of lymph node disease, and type of procedures required for completion of surgery.…”
Section: Discussionmentioning
confidence: 84%
“…Different techniques have been described for robotic AL, to improve surgical outcome, even in challenging situations including patients with: obesity, presence of lymph nodes metastases, necessity to remove infrarenal aortic nodes up to the renal vein; presence of anatomical variations of vessels in the aortic area; and history of previous surgery or neoadjuvant treatments. Recently, a prospective randomized multicenter study (STELLA Trial) concluded that extraperitoneal and transperitoneal approaches to laparoscopic and robotic AL provide similar perioperative outcomes and lymph node yields . The authors of this study also concluded that factors to be taken into account for choosing between extraperitoneal versus transperitoneal approach primarily include patient habitus, site of lymph node disease, and type of procedures required for completion of surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Included studies. A total of seven studies, one randomized control trial and six retrospective trials, which included 608 patients who underwent para-aortic TLL versus ELL, were finally included in the present systematic review (13)(14)(15)(16)(17)(18)(19). Among them, 329 patients underwent TLL, while the remaining 279 patients comprised the ELL group.…”
Section: Resultsmentioning
confidence: 99%